2009
DOI: 10.1002/elsc.200900011
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a combined activated carbon prefilter and biotrickling filter system treating variable ethanol and ethyl acetate gaseous emissions

Abstract: The removal of a 1:1 by weight mixture of ethanol and ethyl acetate was studied in a gas phase biotrickling filter running under conditions that simulated industrial emissions from the flexographic sector, i.e. discontinuous loading (twelve hours per day and five days per week) and oscillating concentration of the inlet stream. Three sets of experimental conditions were tested in which empty‐bed residence time varied from 60 to 25 s (inlet loads from 50 to 90 g C m−3 h−1). The biotrickling filter reached a max… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 15 publications
0
13
0
1
Order By: Relevance
“…Therefore, biomass continued developing although the bioreactor was not fed, meaning that the upper packing material retains that pollutant delivered from the lower layers, saturating the support. Previous studies have observed that pollutant desorption from a granular activated carbon served as an extra source of substrate to a biotrickling filter (Sempere et al 2009). In the present case, although the elimination capacities are practically constant (around 300 g m -3 h -1 ) before and after each feeding stop, the amount of carbon dioxide produced is enhanced after each stopping, indicating that the fraction of pollutant biodegraded is higher during the operation at expenses of pollutant adsorbed.…”
Section: Sorption and Biodegradation Processes Interactionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, biomass continued developing although the bioreactor was not fed, meaning that the upper packing material retains that pollutant delivered from the lower layers, saturating the support. Previous studies have observed that pollutant desorption from a granular activated carbon served as an extra source of substrate to a biotrickling filter (Sempere et al 2009). In the present case, although the elimination capacities are practically constant (around 300 g m -3 h -1 ) before and after each feeding stop, the amount of carbon dioxide produced is enhanced after each stopping, indicating that the fraction of pollutant biodegraded is higher during the operation at expenses of pollutant adsorbed.…”
Section: Sorption and Biodegradation Processes Interactionmentioning
confidence: 99%
“…Dampening the fluctuating concentrations has been a recent research objective in order to enhance the reliability of biofilters to promote their application at real scale (Alvarez-Hornos et al 2008;Sempere et al 2009). Most of studies using activated carbon as packing material focused on placing a separate carbon column before the biofilter, preventing the presence of water to ensure a stable pollutant concentration to degrade in a posterior biofilter (Weber & Hartmans 1995).…”
Section: Introductionmentioning
confidence: 99%
“…The number of studies simulating industrial emissions has increased, aimed at proving the viability or adjusting the operating conditions of the technologies at an industrial scale. These experiments have involved treating mixtures of compounds [11], applying starving periods [12,13] or using transient conditions with or without activated carbon prefilters coupled to the bioreactor in order to operate the system under more stable conditions [14,15]. However, the technology must progress further before its use at an industrial scale, with few studies in the literature on pilot or industrial prototypes [16][17][18][19], and to facilitate this scale-up it is necessary to keep studying the process at the laboratory scale.…”
Section: Introductionmentioning
confidence: 97%
“…The adsorbed pollutant can be used by the microorganisms as a secondary substrate source. Thus, the system can treat inlet flows with sudden pollutant variation, typically found in industrial facilities, avoiding starvation periods . This key parameter has been established in several water treatments by MBR studies .…”
Section: Introductionmentioning
confidence: 99%